Avaliação da resistência à corrosão da liga 2024-T351 soldada por FSW Friction Stir Welding - Busquim, Thaís de Paula (2007)
The corrosion resistance of aluminum alloy can be impaired due to intermetallic precipitation during thermal treatment to improve mechanical properties. This work investigates the corrosion resistance of aluminum alloy 2024-T351 and the joint welded by FSW. Microstructural analysis and microhardness tests were made. Intergranular corrosion tests according to ASTM G110-97, exfoliation corrosion tests according to ASTM G 34-01 and stress corrosion cracking in 3.5% NaCl according to ASTM G 129-00, were carried out. Anodic behavior was evaluated by potentiodynamic polarization measurements in 3.5% NaCl solution. It was not detected intermetallic precipitates by electron and optical microscopy. It was also detected that the joint was more severe attacked than the base metal by intergranular corrosion and exfoliation tests. The welded joint was susceptible to stress corrosion cracking in tests carried out with low nominal strain rate of 10-7 s-1. Base metal and the joint in tests carried out in air and in 3.5% NaCl at strain rate of 10-6 s-1 showed ductile behavior, while the joint with strain rate of 10-7 s-1 showed fragile behavior. The polarization test in chloride medium of aluminum alloys didn t show passive breakdown what make difficult to determinate the pitting potential. Polarization curves indicated that the welded joint had lower current density and higher potential than the base metal. In lower potentials pitting was formed majoritary at grain boundaries